Criticial Limb Ischemia: Epidemiology - Davies, Mark G. (The Methodist Hospital, Houston, Texas, 2012)
Critical limb ischemia is found in 12% of the U.S. adult population. Its clinical presentation varies from no symptoms to intermittent claudication, atypical leg pain, rest pain, ischemic ulcers, or gangrene. Those with critical limb ischemia have a high incidence of cardiovascular comorbidities that reflect a significant systemic atherosclerotic burden; they have increased functional impairment and increased rates of functional decline compared with persons without critical limb ischemia. Interventions for critical limb ischemia and the impact of major amputation have a significant social and economic impact. At 1 year, 25% of patients will be dead, 30% will have undergone amputation, and only 45% will remain alive with both limbs. At 5 years, more than 60% of patients with critical limb ischemia will be dead.